2020
DOI: 10.1007/978-3-030-58920-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mode Reasoning in Model Based Safety Analysis

Abstract: Failure Mode Reasoning (FMR) is a novel approach for analyzing failure in a Safety Instrumented System (SIS). The method uses an automatic analysis of an SIS program to calculate potential failures in parts of the SIS. In this paper we use a case study from the power industry to demonstrate how FMR can be utilized in conjunction with other model-based safety analysis methods, such as HiP-HOPS and CFT, in order to achieve a comprehensive safety analysis of SIS. In this case study, FMR covers the analysis of SIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The above equation means that if the output o is False by fault then either one of its inputs to the OR gate, i.e., 8 shows the results of FOR P V , FOR ST EAM , and SAIDI based on FMR analysis using the assumed failure rates of the power plant components. According to Jahanian et al [11], the soundness of the obtained FMR equations (Eq. 21 to Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above equation means that if the output o is False by fault then either one of its inputs to the OR gate, i.e., 8 shows the results of FOR P V , FOR ST EAM , and SAIDI based on FMR analysis using the assumed failure rates of the power plant components. According to Jahanian et al [11], the soundness of the obtained FMR equations (Eq. 21 to Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Jahanian in [10] has proposed a new technique called Failure Mode Reasoning (FMR) for identifying and quantifying the failure modes for safety-critical systems at the subsystem level. However, according to Jahanian [11], the soundness of the FMR approach needs to be proven mathematically.…”
Section: Introductionmentioning
confidence: 99%
“…where Table 8 shows the probabilistic results of FOR PV , FOR STEAM , and SAIDI based on FMR analysis using the assumed failure rates of the power plant components. According to Jahanian et al [11], the soundness of the obtained FMR equations (Eq. 6 to Eq.…”
Section: ) F or Analysismentioning
confidence: 99%
“…Similarly, Jahanian in [10] has proposed a new technique called Failure Mode Reasoning (FMR) for identifying and quantifying the failure modes for safetycritical systems at the subsystem level. However, according to Jahanian et al [11], the soundness of the FMR approach needs to be proven mathematically.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent project [18] we examined a larger case study where we integrated FMR with other model-base analysis methods HiP-HOPS [26] and CFT [20]. We demonstrated that not only is FMR able to handle larger examples with precision, but its output can also be of value to other safety analysis tools that are designed to model generic systems but not programs.…”
Section: Fmr In Practicementioning
confidence: 99%